Implementation of Midtrans Payment Gateway on the Zumii Store Game Top-Up Platform Using the Laravel Framework - Meilana Refa Permana Permana; Ridho Muktiadi; Agung Purwo Wicaksono; Mukhlis Prasetyo Aji (Politeknik Piksi Ganesha Indonesia, 2025)
This study discusses the development of a responsive website for the Zumii Store Game Top-Up Platform using the prototyping method. The Research was motivated by the need to improve the efficiency of top-up transaction, which were previously handled manually and were prone to eror. The system was developed iteratively using the prototyping approach involving direct user feedback at every stage. The result show that the implemented system can facilitate faster, more accurate, and easily accessible digital ordering, order tracking, and payment processes via both desktop and smartphone devices. Integration with the Midtrans payment gateway also accelerates payment verification and automates product delivery. The adoption of responsive web design and prototyping method has been proven to improve quality and minimize transaction error on the Zumii Store game Top-Up platform.